2019
DOI: 10.1161/jaha.118.011183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arteriovenous Fistula on Blood Pressure in Patients With End‐Stage Renal Disease: A Systematic Meta‐Analysis

Abstract: Background Central arteriovenous fistula ( AVF ) creation is under investigation for treatment of severe hypertension. We evaluated the effects of AVF for initiation of hemodialysis on systolic, diastolic, and mean arterial blood pressure in patients with end‐stage renal disease. Methods and Results Data search included PubMed, Web of Science, and the Cochrane Library. A systematic review and meta‐analysis of peer‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…In patient with AVF, vasodilatation in the contralateral arm through non-endothelial pathways has been described 24 , suggesting a systemic vasodilatory effect of AVF creation. In this regard, a recent meta-analysis shows a significant reduction of BP following AVF creation in ESKD patients 25 . AVF may also alter kidney function through hemodynamics effects, as an AVF is considered a high flow, low-resistance and highcompliance compartment added to the cardiovascular system 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In patient with AVF, vasodilatation in the contralateral arm through non-endothelial pathways has been described 24 , suggesting a systemic vasodilatory effect of AVF creation. In this regard, a recent meta-analysis shows a significant reduction of BP following AVF creation in ESKD patients 25 . AVF may also alter kidney function through hemodynamics effects, as an AVF is considered a high flow, low-resistance and highcompliance compartment added to the cardiovascular system 26 .…”
Section: Discussionmentioning
confidence: 99%
“…30 In a recent meta-analysis, it was shown that creation of dialysis AVF reduced SBP, DBP and MBP by estimated average of 8.7, 5.9 and 6.6-mm Hg respectively. 31 This observation is also in line with the use of ROX arteriovenous coupler, which is used to create an AVF between distal external iliac vein and artery, and which has been shown to reduce the ambulatory SBP by an average of 13.5 mm Hg in a group of patients with resistant hypertension 32 . Indeed, epidemiological observational studies using administrative databases show that hemodialysis with an AVF gives a better survival advantage over the use of central venous catheters.…”
Section: Discussionmentioning
confidence: 59%
“…However, AVF creation was reportedly associated with hemodynamic changes because of the reduced peripheral resistance [12] , and increased right ventricular preload and left ventricular afterload [13] . In addition, AVF creation also significantly decreased blood pressure in end-stage renal disease [14] . Based on these reports, the increase in AVF blood flow in acute response to PTA procedure might lead to hemodynamic instability of the systemic circulation, and systemic oxygenation, including that within the brain, is likely to decrease because of the decrease in oxygen supply to the systemic tissues.…”
Section: Discussionmentioning
confidence: 89%